Residents’ perceptual analysis on liveability in the planned housing estates of nigeria: empirical evidence from niger state - Mohit, Mohammad Abdul; Sule, , Abass Iyanda (Centre for Research Initiative, Liberal Arts and Social Sciences. Universiti Sains Malaysia, 2015)
The government of Nigeria and the state government of Niger in particular, are committed to the development of housing, especially for the low-income group in the state. The housing estates as popularly called have housed many families of the low-income group in the state, however, till to date no effort have been made to understand the perception of the beneficiaries about the liveability of their housing estate. This paper intends to focus on the state of liveability of three public low-income housing estates in Minna, Niger State, Nigeria and the investigation used data derived from a pool of household surveys with 366 respondents. This paper used survey research design to unveil the challenges confronting the residents of the selected housing estates. The residents’ perception of liveability was assessed through five dimensions - housing unit characteristics, economic vitality, security, neighbourhood facilities and social interaction. Data elicited from the structured questionnaire administered were subjected to descriptive statistics, factor analysis and structural modelling. The results show that the respondents were dissatisfied with most of the neighbourhood facilities in the housing estates. Hence, to improve the liveability of these housing estates, this paper recommends rehabilitation of the neighbourhood facilities in these housing estates. Also, the neighbourhood facilities management strategy should be put in place by the appropriate authority in collaboration with the residents of these housing estates.